Analisis Kesetaraan Gender terhadap Dakwah Rasulullah SAW (Kajian Sejarah Islam) - Ulfa Damayanti; Hasnani Siri; Nurhikmah Nurhikmah; Musyarif Musyarif; St. Aminah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2020)
Gender issues are being discussed, especially regarding the roles of men and women in domestic and public sectors. How about the issue of gender equality during the da’wah period of the Prophet. This paper discusses gender equality in the da’wah of the Prophet Muhammad. Qira'ah Mubadalah (a progressive interpretation of gender equality in Islam) is the main source of literature research with a historical approach used to analyze gender equality during the time of da’wah by Prophet Muhammad. This research aims to provide a picture to society about the application of gender equality in modern era. Since the inception of Islam, Rasulullah SAW. has provided an understanding of equality for men and women. The da’wah of Rasulullah SAW. regarding equality is evident from the roles of men and women who both took allegiance, migrated, and were involved in Islamic wars. It can be said that there is gender equality in the preaching of the Prophet Muhammad. Besides that, women also do various jobs that at that time are in the public sector. This indicates that women are not only bound by domestic roles, as well as men who are not only bound by public roles. Gender equality is no longer a polemic to get a position for men and women because each has the opportunity and the role to be involved in public and domestic activities.